Radix Pseudostellaria polysaccharides alleviate sepsis-induced liver injury by modulating the gut microbiota via the TLR4/NF-κB pathway - Wang, Zhuolin; Lin, Xiaohong; Wu, Jianfeng; Su, Chanyuan; Luo, Yukun; Yu, Guangwei (Frontiers in Pharmacology, 2025)
BackgroundSepsis-induced liver injury (SLI) is a life-threatening complication with limited therapeutic options. Radix Pseudostellariae polysaccharides (RPPS), a component of traditional Chinese medicine, exert immunomodulatory, anti-inflammatory, and antioxidant properties. Herein, we investigated the therapeutic effects and mechanisms of RPPS on SLI.MethodsA murine sepsis model was established using cecal ligation and puncture. Mice were pretreated with RPPS or saline for 14 days. Subsequently, multi-omics integration—including metagenomics, proteomics, and network pharmacology—was employed to elucidate the mechanisms of RPPS. Liver injury was assessed via serum biomarkers, histopathology, and transmission electron microscopy, while intestinal barrier integrity was evaluated through histopathological analysis. Gut microbiota composition and functional pathways were examined using metagenomic sequencing. Furthermore, Kyoto Encyclopedia of Genes and Genomes enrichment analyses of gut microbiota, liver proteomics, and network pharmacology data were integrated to predict key target pathways, which were experimentally validated in mice.ResultsRPPS pretreatment significantly improved survival, reduced liver injury markers, attenuated hepatic necrosis and inflammation, and restored intestinal barrier integrity. RPPS also modulated the gut microbiota by enriching beneficial taxa and suppressing pathogens. Multi-omics integration identified the toll-like receptor 4 (TLR4)/nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway as the core mechanism, and experimental validation confirmed that RPPS inhibited TLR4 membrane expression, MyD88/IKKα/β activation, NF-κB p65 phosphorylation, and nuclear translocation. In conclusion, RPPS alleviates SLI by protecting the intestinal barrier, modulating gut microbiota, and suppressing the TLR4/NF-κB signaling pathway.ConclusionThis study provides a scientific foundation for RPPS as a potential therapeutic candidate in sepsis treatment.